2017
DOI: 10.1016/j.virol.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation of influenza A PB2 sequences reveals potential target sites for small molecule inhibitors

Abstract: The influenza A basic polymerase protein 2 (PB2) functions as part of a heterotrimer to replicate the viral RNA genome. To investigate novel PB2 antiviral target sites, this work identified evolutionary conserved regions across the PB2 protein sequence amongst all sub-types and hosts, as well as ligand binding hot spots which overlap with highly conserved areas. Fifteen binding sites were predicted in different PB2 domains; some of which reside in areas of unknown function. Virtual screening of ~50,000 drug-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
5
11
0
Order By: Relevance
“…The structural analysis of the modeled proteins combined with the sequence conservation analysis revealed several findings. First, we found that the mutated residues tended to locate on the protein's surface, supporting previous observations in other families of RNA viruses that the core residues of viral proteins were more conserved than the surface residues [49,69,70]. Furthermore, in a substantial number of proteins, distributions of mutated positions exhibited spatial patterns, with groups of mutations found to form clusters on the protein surfaces ( Figure 2).…”
Section: Structural Genomics and Interactomics Analysis Of Sars-cov-2supporting
confidence: 88%
“…The structural analysis of the modeled proteins combined with the sequence conservation analysis revealed several findings. First, we found that the mutated residues tended to locate on the protein's surface, supporting previous observations in other families of RNA viruses that the core residues of viral proteins were more conserved than the surface residues [49,69,70]. Furthermore, in a substantial number of proteins, distributions of mutated positions exhibited spatial patterns, with groups of mutations found to form clusters on the protein surfaces ( Figure 2).…”
Section: Structural Genomics and Interactomics Analysis Of Sars-cov-2supporting
confidence: 88%
“…The structural analysis of the modeled proteins combined with the sequence conservation analysis revealed several findings. First, we found that the mutated residues tend to locate on the protein's surface, supporting the previous observations in other families of RNA viruses that the core residues of viral proteins are more conserved than the surface residues [48,56,57]. Furthermore, in a substantial number of proteins, distributions of mutated positions exhibited spatial patterns, with groups of mutations found to form clusters on the protein surfaces ( Fig.2).…”
Section: Structural Genomics and Interactomics Analysis Of 2019-ncovsupporting
confidence: 89%
“…The structural analysis of the modeled proteins combined with the sequence conservation analysis revealed several findings. First, we found that the mutated residues tend to locate on the protein's surface, supporting previous observations in other families of RNA viruses that the core residues of viral proteins are more conserved than the surface residues [48,56,57]. Furthermore, in a substantial number of proteins, distributions of mutated positions exhibited spatial patterns, with groups of mutations found to form clusters on the protein surfaces ( Fig.2).…”
Section: Structural Genomics and Interactomics Analysis Of Sars-cov-2supporting
confidence: 88%